Norm-Constrained Least-Squares Solutions to the Matrix Equation AXB=C - An-bao Xu; Zhenyun Peng (Abstract and Applied Analysis)
An iterative method to compute the least-squares solutions of the matrix AXB=C over the norm inequality constraint is proposed. For this method, without the error of calculation, a desired solution can be obtained with finitely iterative step. Numerical experiments are performed to illustrate the efficiency and real application of the algorithm.